Eksplorasi Persepsi Ibu terhadap Penggunaan Gadget pada Balita: Studi Fenomenologi - Nabila Dwi Handayani; Filia Sofiani Ikasari; Raihana Norfitri; Tiara Lani (An Idea Health Journal, 2026)
Background: The rapid advancement of digital technology has increased toddlers exposure to gadget, making them an integral part of daily life. While gadgets may offer educational benefits when used appropriately, excessive and unsupervised use can negatively affect children’s physical, cognitive, language, social, and emotional development. Mothers, as primary caregivers, play a crucial role in regulating toddlers’ gadget use, guided by their perceptions and parenting practices.Methods: This study employed a qualitative descriptive phenomenological design to explore mothers’ perceptions of gadget use among toddlers in the working area of Banjarbaru Selatan Public Health Center. Twelve mothers with toddlers were selected using purposive sampling until data saturation was achieved. Data were collected through in-depth interviews and analyzed using Colaizzi’s method, including familiarization with transcripts, identification of significant statements, formulation of meanings, theme clustering, comprehensive description, and participant validation to ensure trustworthiness. Result:Five main themes emerged: mothers’ responses to gadget use, reasons for providing gadgets, duration of gadget use, perceived impacts of gadget use, and strategies to divert children from gadgets. Mothers perceived gadgets both as helpful tools for calming and entertaining children and as potential sources of developmental risks. Gadget use was often driven by situational needs, such as parental busyness or limited caregiving support. Prolonged use was associated with behavioral changes, emotional dysregulation, and delayed language development, particularly when parental supervision was limited. Conversely, active parental involvement, content selection, and time regulation were perceived as protective factors. Mothers also reported various diversion strategies, including interactive play, outdoor activities, and the provision of alternative toys. Conclusion: Gadget use among toddlers is increasingly unavoidable; however, its impact largely depends on maternal perceptions, supervision, and regulation practices. Strengthening mothers’ awareness and caregiving strategies is essential to minimize negative effects and promote optimal toddler development.